Strategi Fun Learning dalam Meningkatkan Pemasaran Pendidikan Islam di Era 4.0 - Aisyah Amalia Putri; Subiyantoro Subiyantoro (ISLAMIKA, 2022)
The purpose of this research is to find out fun learning strategies that are designed attractively according to students' interests to achieve fun learning and potentially in improving the marketing of Islamic education in the 4.0 era. The research approach used is descriptive qualitative research. The type of research used is literature. The results of this study show that one of the characteristics of education in the 4.0 era in the learning process is learning that provides opportunities for students to learn as well as their respective interests and learning speed (student center). Islamic education in the era of 4.0 needs to disrupt itself with proper learning to maintain the existence and marketing of Islamic education throughout the ages. Fun learning strategies are steps to foster a sense of love and motivation for learners to learn. The conclusion of this study is the ability of fun learning strategies to improve the marketing of Islamic education in the 4.0 era through good management by maintaining the existence of Islamic education, designing Islamic education marketing using fun learning strategy learning models, and forming good customer loyalty to students.